PENGARUH GROWTH OPPORTUNITY DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PROPERTI DAN REAL ESTATE DI BURSA EFEK INDONESIA - Febiawanticha, Resma; Wahyuni, Ika; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The purpose of this study is to find out growth opportunity has a significant effect on capital structure, profitability has a significant effect on capital structure, growth opportunity has a significant effect on firm value, profitability has a significant effect on firm value, capital structure has a significant effect on firm value, growth opportunity has a significant effect on firm value through capital structure, profitability has a significant effect on firm value through capital structure. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM) Based on the results of the study, it is known that growth opportunity has a positive but not significant effect on capital structure. Profitability has a positive and significant effect on capital structure. Growth opportunity has a positive and significant effect on firm value. Profitability has a positive and significant effect on firm value. Capital structure has a positive and significant effect on firm value. Growth opportunity has a positive but not significant effect on firm value through capital structure. Profitability has a positive and significant effect on firm value through capital structure.